An ANALYSIS: INDONESIA’S NEW NORMAL POLICY IMPLEMENTATION DURING COVID-19 AND ITS IMPACT ON ECONOMIC ASPECT - Helen Dian Fridayani; Muhammad Iqbal (Universitas Jenderal Ahmad Yani, 2020)
This study aims to analyze the new normal policy implementation during Covid-19 to deliverance the economy of Indonesia. New normal is one of the options to become a milestone in Indonesia's economic revival. The government has decided to run a new normal policy to encourage economic recovery. Although, the Covid-19 pandemic has not shown any signs of ending. Previously the handling of Covid-19 in Indonesia by seeking social distancing to large-scale social restrictions. However, this policy seems to make the economy in Indonesia stuck, so the government's step is to implement new normal. The method used in this study is qualitative-descriptive, with secondary data obtained from various sources such as government websites, journals, books, and online media. As a result, this new normal policy is aimed at all business sectors. To support this policy, the government has made working guidelines in new normal situations. If economic activity returns, the most noticeable impact will be reduced unemployment and the availability of various jobs. Therefore, people's purchasing power is expected to recover as before the Covid-19 pandemic emerged. New normal activity amid the Covid-19 pandemic is like two sides of a coin. On the one hand, there is the potential to boost the economy; however, there is a risk of increasing the coronavirus's positive cases. This study found that health protocols can be easily formulated, but implementation may not be comfortable in the field. For this reason, various multidisciplinary studies need to be considered by the government in implementing the new normal policy.